2021
DOI: 10.1002/adma.202105761
|View full text |Cite
|
Sign up to set email alerts
|

A Single‐Droplet Electricity Generator Achieves an Ultrahigh Output Over 100 V Without Pre‐Charging

Abstract: various scattered and irregular energy sources in the natural environment. [10] Although this type of energy is small, it is distributed extremely widely. If utilized reasonably, it will certainly make a significant contribution to human energy strategy.Coupled with contact electrification and electrostatic induction, Prof. Wang's group first invented the triboelectric nanogenerator (TENG) in 2012. [11] Presently, as the mainstream technology for energy harvesting, TENG has shown great application prospects in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(47 citation statements)
references
References 31 publications
0
47
0
Order By: Relevance
“…The output performance of the SHD-TENG is related to the maximum diffusion area of the droplet when it contacts the top electrode ( S max ) and the maximum area change rate of the diffusing droplet (d S /d t max ). 50,51 As α increased, S max reduced, which is not conducive to good output performance. On the contrary, d S /d t max got larger with α increasing which is beneficial to the improvement of the output performance (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The output performance of the SHD-TENG is related to the maximum diffusion area of the droplet when it contacts the top electrode ( S max ) and the maximum area change rate of the diffusing droplet (d S /d t max ). 50,51 As α increased, S max reduced, which is not conducive to good output performance. On the contrary, d S /d t max got larger with α increasing which is beneficial to the improvement of the output performance (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The variation in droplet-solid contact area is critical for the generated current (I) of the droplet-based triboelectric nanogenerator (D-TENG, Figure 4d): I ∼ dS/dt. [30][31][32][33][34][35] This is because when a droplet impacts on a dielectric substrate (such as PTFE), the capacitance of the formed hybrid electrical double layer changes with the droplet-solid contact area. [36][37][38][39][40][41] Therefore, the multi-droplet-spring can be utilized to optimize the performance of the droplet-based TENG.…”
Section: Resultsmentioning
confidence: 99%
“…The instantaneous power density was several orders of magnitude higher than before. Zhang et al (2021), as shown in Figure 8A, introduced an electric doublelayer capacitor at the liquid-solid contact electrification interface of DEG, and established an equivalent circuit model of DEG with a switching effect, achieving a power output of two orders of magnitude higher than the previous electrostatic induction power generation without polarizing the solid surface. As shown in In terms of liquid-solid contact electrification based triboelectric nanogenerator for water drop energy and ocean energy collection, as shown in Figure 8C, Gang et al (2021) prepared textile TENG which can collect raindrop energy and generate a voltage of 4.3 V and a current of 6 μA.…”
Section: Applicationsmentioning
confidence: 99%